Perspectives on Developing Healthcare Managers in Africa: The Strathmore Business School's Healthcare Management Programme - Sammut, Stephen M.; Ngoye, Ben (Frontiers in Public Health, 2019)
A substantial shortage of qualified healthcare professionals in Africa continues, but it is now apparent that professionally trained healthcare managers are an equally important need. Health facilities in Africa typically promote physicians into the role of general manager, but physicians and their lay counterparts routinely admit to being ill-prepared for roles as leaders of health systems, healthcare facilities and other services. Few, if any, degree programmes for healthcare management—be they master's in hospital administration or specialized MBA programmes— are available in these regions. And while many master's in public health programmes exist, inclusion of healthcare management content is often an afterthought. This article presents a prototype programme that was designed to address this gap. This comprehensive healthcare management MBA programme that was established at the Business School of Strathmore University in Nairobi, Kenya in 2013 was built around the “Leadership Competencies for Health Care Managers” as promulgated by the International Hospital Federation. The article further presents the development, structure and innovations of the programme, thus providing a blueprint for the development of similar programmes throughout the continent, aimed at addressing the substantial shortage of professionally trained healthcare managers.